Insights Into Excess Mortality During the First Months of the COVID-19 Pandemic From a Rural, Demographic Surveillance Site in Bangladesh - Hanifi, Syed Manzoor Ahmed; Alam, Sayed Saidul; Shuma, Sanjida Siddiqua; Reidpath, Daniel D. (Frontiers in Public Health, 2021)
Background COVID-19 has spread globally and the government of each affected country is publishing the number of deaths every day. This official figure is an underestimate as it excludes anybody who did not die in a hospital, who did not test positive, had a false result or those who recovered on their own without a test. Objective The paper aims to measure the community level excess mortality using a health and demographic surveillance in a rural area of Bangladesh. Method The study was conducted in Matlab, a rural area of Bangladesh, with a Health and Demographic Surveillance System (HDSS) covering a population of 260,000 individuals living in 60,000 households in 142 villages. We examined the mortality in January-April from 2015-2020 and compared the mortality in 2020 with the historical trend of 2015-2019. Between 2015 and 2020, we followed 276,868 people until migration or death, whichever occurred first. We analyzed mortality using crude mortality rate ratio (MRR) and adjusted MRR (aMRR) from a Cox proportional hazard model. Mortality was analyzed according to age, sex, and period. Results During follow-up 3197 people died. The mortality rate per 1000 person-years increased to 12 in 2020 from 10 in 2019. Excess mortally was observed among elderly (65 years and above). The elderly mortality rate per 1000 person-year increased to 110 in 2020 from 80 in 2019, the adjusted mortality rate ratio was 1‧40 (95% CI 1‧19-1‧64). Although an increasing tendency in mortality was observed between 2015 and 2019, it was statistically insignificant. Conclusions The study reported a 28% increase in excess deaths among the elderly population during the first months of the pandemic. This all-cause mortality estimation at the community level will urge policymakers, public health professionals, and researchers to further investigate the causes of death and the underlying reasons for excess deaths in the older age group.